Youths' Literacy Disidentifications in a Secondary Classroom: Contesting Transphobia through Humor in Role-Playing. Issue 7 (July 2020) - Schey, Ryan
Background: Recent decades have seen an increased number of literacy education researchers attending to LGBTQ people and texts in secondary schools, frequently documenting tensions that emerge, such as conflict. However, this research tends to be limited in scope with respect to time, texts, and identities. Moreover, it shows that students tend to face challenges and constraints when attempting to challenge homophobia and transphobia. Focus of Study: In this study, I sought to extend previous scholarship by exploring how students used reading and writing to work within, on, and against normative values and practices in a secondary classroom as they enacted queer activism, efforts I conceptualize as literacy disidentifications. Setting: This study took place at a public urban comprehensive high school that I call Harrison High School, which was in a midsized Midwestern U.S. city. In this manuscript, I focus on one course, a sophomore humanities class that combined English language arts and social studies. Research Design: I conducted a yearlong literacy ethnography at Harrison, acting as a participant observer throughout the high school but focusing on literacy learning contexts, including English language arts classrooms and a GSA (Genders and Sexualities Alliance) club. Data Collection and Analysis: During my participant observation experiences, I constructed field notes. In addition, I made audio and video recordings of classroom lessons, collected documents, and conducted interviews with teachers, students, and administrators. I analyzed these data through an inductive and comparative grounded theory approach. Findings: Drawing on sociocultural perspectives of literacy and language along with queer theories, I conceptualize literacy disidentifications and explore this heuristic through the actions of Imani, a queer youth of color who encountered a schooling context where her activism was frequently shut down. To legitimize and sustain her queer activism, she blended humor with other literacy practices, such as role-playing and signification, which resulted in critiquing, yet not necessarily transforming, transphobia. Conclusions: These findings suggest that educators working to cultivate queer-affirming schools can: sanction conflict and teach youth how to navigate conflict in compassionate and humanizing ways; recognize, rather than squelch, youths' queer activism; teach LGBTQ-inclusive curricula, especially curricular texts that foreground the lives and perspectives of trans people; and broaden the range of youth literacy practices valued in classroom lessons.